Technical Note—Minimizing Average Flow Time with Parallel Machines - Horn, W. A. (Operations Research, 1973)
This note shows that the assignment and sequencing of single-operation jobs in a parallel-machine environment can be formulated as an assignment problem. Means for reducing the size and computational difficulty of this problem are identified.